Comparison of postoperative acute kidney injury between ileal conduit and neobladder urinary diversions after radical cystectomy: A propensity score matching analysis. Issue 36 (September 2016) - Joung, Kyoung-Woon; Kong, Yu-Gyeong; Yoon, Syn-Hae; Kim, Yeon Ju; Hwang, Jai-Hyun; Hong, Bumsik; Kim, Young-Kug
Abstract : Abstract: Ileal conduit and neobladder urinary diversions are frequently performed after radical cystectomy. However, complications after radical cystectomy may be different according to the type of urinary diversion. Acute kidney injury (AKI) is a common complication after surgery and increases costs, morbidity, and mortality of hospitalized patients. This study was performed to compare the incidence of postoperative AKI between ileal conduit and neobladder urinary diversions after radical cystectomy. All consecutive patients who underwent radical cystectomy in 2004 to 2014 in a single tertiary care center were identified. The patients were divided into the ileal conduit and ileal neobladder groups. Preoperative variables, including demographics, cancer-related data and laboratory values, as well as intraoperative data and postoperative outcomes, including AKI, intensive care unit admission rate, and the duration of hospital stay, were evaluated between the groups. Postoperative AKI was defined according to the Kidney Disease: Improving Global Outcome criteria. Propensity score matching analysis was performed to reduce the influence of possible confounding variables and adjust for intergroup differences. After performing 1:1 propensity score matching, the ileal conduit and ileal neobladder groups each included 101 patients. The overall incidence of AKI after radical cystectomy was 30.7% (62 out of 202) and the incidences did not significantly differ between the groups (27 [26.7%], ileal conduit group vs 35 [34.7%], ileal neobladder group, P = 0.268). Intraoperative data, intensive care unit admission rate, and the duration of hospital stay were not significantly different between the groups. Postoperative AKI did not significantly differ between ileal conduit and neobladder urinary diversions after radical cystectomy. This finding provides additional information useful for appropriate selection of the urinary diversion type in conjunction with radical cystectomy.